2021
DOI: 10.1093/braincomms/fcab240
|View full text |Cite|
|
Sign up to set email alerts
|

Objective biomarkers for clinical relapse in multiple sclerosis: a metabolomics approach

Abstract: Accurate determination of relapses in Multiple Sclerosis (MS) is important for diagnosis, classification of clinical course and therapeutic decision making, The identification of biofluid markers for MS relapses would add to our current diagnostic armamentarium and increase our understanding of the biology underlying the clinical expression of inflammation in MS. However, there is presently no biofluid marker capable of objectively determining MS relapses although some, in particular neurofilament-light chain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…NMR metabolomics is a cheap and rapid analysis method, requiring minimal sample preparation and with the advantage that a host of additional small molecules can be quantified in the same analysis. Indeed, we have shown that NMR metabolomics is able to identify relapse (38), predict conversion (16), and diagnose progression (39) in MS and so, in future, it may be possible to apply multiple tests to a single sample. Future work will develop a chip-based assay to measure only the top biomarkers identified here in the hopes of improving translatability of this method.…”
Section: Discussionmentioning
confidence: 99%
“…NMR metabolomics is a cheap and rapid analysis method, requiring minimal sample preparation and with the advantage that a host of additional small molecules can be quantified in the same analysis. Indeed, we have shown that NMR metabolomics is able to identify relapse (38), predict conversion (16), and diagnose progression (39) in MS and so, in future, it may be possible to apply multiple tests to a single sample. Future work will develop a chip-based assay to measure only the top biomarkers identified here in the hopes of improving translatability of this method.…”
Section: Discussionmentioning
confidence: 99%
“…Altered circulating levels of amino acids and gamma-glutamyl amino acids have been observed in MS patients 2, 3 . A higher serum level of lysine was observed in MS patients when compared to healthy controls 6 , and also in MS patients who are in relapse in comparison to those that are a few months after the last relapse 35 . The pattern for serine is more complex.…”
Section: Discussionmentioning
confidence: 87%
“…The other pathways are mostly related to the acute response except for asparagine pathway. Though its role in multiple sclerosis is unclear, asparagine may have roles in proper immune functioning and asparagine biosynthesis may be one of the main canonical pathways involved in multiple sclerosis [ 33 ]. The inhibition of asparagine endopeptidase greatly enhanced presentation of the myelin basic protein [ 34 ], which plays a key role in pathogenesis of multiple sclerosis.…”
Section: Resultsmentioning
confidence: 99%